Spatial Theory, Temporality and Public Action - Fache, Jacques (European Spatial Research and Policy, 2011)
Innovation and information combined with ICTs constitute a new framework which questions the theories on the functioning of classic space and stresses the need to think of new frames. The principle of acentrality proposed here highlights the role of politics in the structuring of space, as well as the role of temporality. For public planning policies to be relevant, acentrality and temporality must be taken into account.